Who are EU? Ambiguities in the concept of competitivenenss - Strange, Susan (1998)
Argues that it is first necessary to clear up some of the ambiguities in the current debate about European competitiveness if we are to develop a coherent and effective industrial and macroeconomic policy for Europe.